O verbo baleado: imbricamentos éticos e estéticos na representação da violência em Cidade de Deus, de Paulo Lins - Cruz, Cecília Lara da (2014)
This research investigates the connection between ethics and aesthetics in the representation of violence in the novel Cidade de Deus by Paulo Lins. The intense presence of violence in Brazilian history is articulated not only with forms and themes, but also with the ways artists express themselves, including in literature. The so-called crime fiction literature, which Cidade de Deus stands out as an example of, shows violence in an urban context as the main theme. This research aims to contribute to the studies on representations of violence and their meanings in literature and how that advanced Brazilian literary criticism, by analyzing the formal features and thematic aspects of the novel Cidade de Deus. We attempt to analyze the description of violence in the book, especially regarding the limits and representation possibilities within the ethical sphere, considering how it s impossible to represent the catastrophe. Issues we address are: the author s point of view and how he represents it; the outlines for representing extreme situations, which cannot be compared to anything other situation; the fact that the representation of violence brings implications to realism and the insight built by Paulo Lins and the possible connections between the representation of violence in the novel and the concepts of trauma, testimony, and melancholy, the way they have current been used in critical literary. The results show that Cidade de Deus can t be considered a testimonio due to the fact that this genre is set in post-dictatorial Latin America, despite its POV-style (Point of View) content, among other reasons, because it does not present a hesitant and unreliable narrator. We have also demonstrated that the insight s effect, hailed by critics, consists of literary and non-literary aspects and procedures. Moreover, we conclude and try to prove that Lins's novel is irregular, since it occasionally brings the representation of violence in order to encompass multiple meanings; in other times, it brings joy through stereotypical representations of violence. The theoretical framework is grounded in the proposals of Karl Erik Schollhammer, Tania Pellegrini, Jaime Ginzburg, Márcio Seligmann-Silva, Antonio Candido, Beatriz Resende and Hal Foster